Tìm x biết : \(2^{2x+1}+4^{x+3}=4224\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{x}{3}=\dfrac{4}{12}\Rightarrow x=\dfrac{4}{12}\cdot3=\dfrac{12}{12}=1\)
b) \(\dfrac{x-1}{x-2}=\dfrac{3}{5}\) (Điều kiện : \(x\ne2\))
\(\Rightarrow5\left(x-1\right)=3\left(x-2\right)\)
\(\Leftrightarrow5x-5=3x-6\Leftrightarrow5x-3x=-6+5\Leftrightarrow2x=-1\Leftrightarrow x=-\dfrac{1}{2}\)
c) \(2x:6=\dfrac{1}{4}\Leftrightarrow2x=\dfrac{1}{4}\cdot6=\dfrac{6}{4}=\dfrac{3}{2}\Leftrightarrow x=\dfrac{3}{2}:2=\dfrac{3}{2}\cdot\dfrac{1}{2}=\dfrac{3}{4}\)
d) \(\dfrac{x^2+x}{2x^2+1}=\dfrac{1}{2}\)
\(\Rightarrow2\left(x^2+x\right)=2x^2+1\)
\(\Leftrightarrow2x^2+2x=2x^2+1\)
\(\Leftrightarrow2x^2+2x-2x^2=1\Leftrightarrow2x=1\Leftrightarrow x=\dfrac{1}{2}\).
\(a,\Leftrightarrow x^3-8-x\left(x^2-9\right)=1\\ \Leftrightarrow x^3-8-x^3+9x=1\\ \Leftrightarrow9x=9\Leftrightarrow x=1\\ b,\Leftrightarrow8x^3+12x^2+6x+1-8x^3 +12x^2-6x+1-24x^2+24x-1=0\Leftrightarrow1=0\Leftrightarrow x\in\varnothing\)
a) \(\Leftrightarrow x^3-8-x^3+9x=1\)
\(\Leftrightarrow9x=9\Leftrightarrow x=1\)
b) \(\Leftrightarrow8x^3+12x^2+6x+1-8x^3+12x^2-6x+1-24x^2+24x-6=5\)
\(\Leftrightarrow24x=9\Leftrightarrow x=\dfrac{3}{8}\)
PT \(\Rightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)
\(\Rightarrow-4x=-4\) \(\Leftrightarrow x=1\)
Vậy \(x=1\)
Ta có: \(2x\left(x+1\right)-3\left(x+2\right)=x\left(2x-1\right)+4\left(x-2\right)-2\)
\(\Leftrightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)
\(\Leftrightarrow2x^2-x-6=2x^2+3x-10\)
\(\Leftrightarrow2x^2-x-6-2x^2-3x+10=0\)
\(\Leftrightarrow-4x+4=0\)
\(\Leftrightarrow-4x=-4\)
hay x=1
Vậy: x=1
3:
a: 3^x*3=243
=>3^x=81
=>x=4
b; 2^x*16^2=1024
=>2^x=4
=>x=2
c: 64*4^x=16^8
=>4^x=4^16/4^3=4^13
=>x=13
d: 2^x=16
=>2^x=2^4
=>x=4
\(2^{2x+1}+4^{x+3}=4224\)
\(2^{2x}.2+4^x.64=4224\)
\(2^{2x}.2+2^{2x}.2^6=4224\)
\(2^{2x}.\left(2+2^6\right)=4224\)
\(2^{2x}=64\)
\(2^{2x}=2^6\)
\(\Leftrightarrow2x=6\)
\(\Leftrightarrow x=3\)